Time indices of long-latent auditory evoked potentials in the workers of “noise” professions at the process of preparation and bottling of non-alcohol and weak alcohol beverages (Environment & Health, 2016)
Objective. We studied the functional state of the acoustic analyzer cortex region by the data of long-latent auditory evoked potentials (LAEP) of the workers of “noise” professions, employed at the Obolon factory, taking into account the hygienic labour conditions.Methods and materials. We present a hygienic assessment of noise, microclimate, and lighting on the working places of the operators. The measurements were performed with the help of audiometer "Larson Davis 800B", globe thermometer “Tensor 41”, catathermometer (F 564), luxmeter “U-116”. We carried out the study of temporary indices of long-latent auditory evoked potentials in 37 workers of “noise” professions at the Obolon factory (mainly the operators engaged in beverage bottling). The control group consisted of 15 somatically and otologically healthy people not affected the industrial noise.Results. According to the “Hygienic Classification of Labour…” № 248 of 08.04.2014, approved by the Decree of the Ministry of Public Health of Ukraine, by the noise levels at different working places the labour conditions of the workers, engaged in beverage bottling, may belong to 3.1 labour conditions class (harmful conditions of the 1-st degree) and 3.2 class (harmful conditions of the 2-nd degree); by the temperature of the air – to 2 (permissible), 3.1 (harmful conditions of the 1-st degree) and 3.2 (harmful conditions of the 2-nd degree) labour conditions classes; by the labour process difficulty and its intensity – to 2 (permissible) and 3.1 (harmful conditions of the 1-st degree) labour conditions classes. As a whole the labour conditions of the operators, engaged in the beverage bottling, may be referred to the 3.2 danger class (harmful conditions of the 2-nd degree).At the analysis of the peak latent periods of P1, N1, Р2 and N2 components of the long-latent auditory evoked potentials under ipsilateral stimulation by 1 kHz tone in the main group a reliable increase in length of the peak latent period of the N2 component in the workers of “noise” professions was detected in comparison with the control one.Conclusions. A reliable (P
Keywords: long-latent auditory evoked potentials; workers of “noise“ professions; acoustic analyzer cortex region